Sistem Informasi Pengelohan Data Pasien Rawat Inap Berbasis SMS Gateway - Haryanto Haryanto; Bambang Priyatmoko (INFORMATIKA, 2015)
Puskesmas Gesi is a public health service centre institution under Sragen  Regency  Government  having  responsibility  in  public  health  sector. Medical data service and process still run less effectively because all of activities are carried out manually either recording in the form of document or archive. Therefore that was less effective and error often occurs. This research and system design employed library study with pieces analysis method and UML design. Library study was a process of looking for theoretical basic sources to be discussed in this topic. The analysis method used was  to  analyze  the  performance  of  Puskesmas  by  conducting  survey  and identifying the information need. UML design represented the system plot to be made  with  use  case,  class  diagram,  activity  diagram,  interface  designing, database designing using SQL Server 2000, report writing using crystal report 8.5, and supporting software using Microsoft Visual Basic 6.0. This design and development of Inpatient Data Processing Information system facilitated the medical personnel in processing and recording medical personnel  data,  patient  data,  drug  data,  outpatient  data,  inpatient  data,  and report.Keywords: Pieces Method, UML, SQL, Crystal Report and Visual Basic 6.0